2006
DOI: 10.1016/j.pscychresns.2006.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of schizophrenia by diffusion weighted imaging

Abstract: A novel magnetic resonance imaging method was used to determine whether it is feasible to detect early signs of cortical atrophy among individuals who are at high risk for developing schizophrenia. Fifteen individuals at high-risk for schizophrenia and 15 of their first degree relatives diagnosed with schizophrenia were compared with controls (n=25) who did not have a family history of psychiatric illness or psychiatric hospitalizations. On the basis of a voxelwise analysis of apparent diffusion coefficient (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 17 publications
3
40
0
1
Order By: Relevance
“…In general, our findings are consistent with previous MRI studies from five independent samples (Pittsburgh, Edinburgh, Ulm, Bethesda and Orangeburg/New York) of genetic highrisk individuals still within the age range for developing schizophrenia (DeLisi et al 2006;Gogtay et al 2003;Job et al 2003;Job et al 2005b;Job et al 2006;Keshavan et al 1997;Keshavan et al 2002b ;Lawrie et al 1999;Lawrie et al 2001;Lawrie et al 2002;Rajarethinam et al 2004;Schreiber et al 1999). Even though these young relatives do not have psychotic disorders, they have volume deficits in similar brain regions as schizophrenia patients -albeit less severe.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, our findings are consistent with previous MRI studies from five independent samples (Pittsburgh, Edinburgh, Ulm, Bethesda and Orangeburg/New York) of genetic highrisk individuals still within the age range for developing schizophrenia (DeLisi et al 2006;Gogtay et al 2003;Job et al 2003;Job et al 2005b;Job et al 2006;Keshavan et al 1997;Keshavan et al 2002b ;Lawrie et al 1999;Lawrie et al 2001;Lawrie et al 2002;Rajarethinam et al 2004;Schreiber et al 1999). Even though these young relatives do not have psychotic disorders, they have volume deficits in similar brain regions as schizophrenia patients -albeit less severe.…”
Section: Discussionsupporting
confidence: 91%
“…Despite this limitation, we still found smaller frontal GM volumes in relatives, which is consistent with the Gogtay et al study where siblings of childhood-onset schizophrenia patients also had smaller frontal GM and total GM than healthy controls (Gogtay et al 2003). Using a novel and potentially more sensitive MR imaging technique of diffusion weighted imaging, DeLisi et al found nonpsychotic young relatives of schizophrenia probands had increased apparent diffusion coefficients suggestive of volume reductions in the left parahippocampal, lingual, superior frontal and middle frontal gyri (DeLisi et al 2006). …”
Section: Discussionsupporting
confidence: 90%
“…Speed of diffusion is quantified by the apparent diffusion coefficient (ADC), also referred and closely related to MD. Diffusion MR imaging is a noninvasive imaging method that provides information about microstructure and cytoarchitecture of the white matter [33][34][35][36][37][38][39][40]. Diffusion MR imaging has widely been used in assessment of stroke [33], genetic disorders [34], degenerative diseases [35] and psychiatry disorders such as schizophrenia [36][37][38][39] and bipolar disorders [40].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no DTI studies in UHR patients have been reported. One diffusion-weighted study in first-degree relatives of schizophrenia patients found diffusion abnormalities in gray matter structures not detectable with conventional MRI [19] . In chronic schizophrenia patients, several DTI studies found reduced anisotropy in numerous brain regions [20][21][22][23] .…”
mentioning
confidence: 99%